Concurrent multiple sclerosis and amyotrophic lateral sclerosis: where inflammation and neurodegeneration meet? - Li, G; Esiri, M; Ansorge, O; DeLuca, G (2012)
The concurrence of multiple sclerosis (MS) and amyotrophic lateral sclerosis (ALS) is exceedingly rare and the pathological features have not been examined extensively. Here we describe the key pathological features of a 40 year old man with pathologically confirmed concurrent MS and ALS.This is the most pathologically illustrative case of coincident MS and ALS demonstrating inflammatory and neurodegenerative features characteristic of each disease, and is the first to exhibit the presence of TDP-43 inclusions in this clinical entity. The intricate relationship between neuroinflammation and neurodegeneration in these diseases is discussed.